(untitled) (Research, Society and Development, 2021)
The cosmetic market has invested in supplying the interests of the Wellness population group that seeks a healthier and more sustainable lifestyle for the environment, leading to the enhancement of plant assets and their incorporation into cosmetic and hygiene products. In this sense, the present study aims to address the employability of oils from Pilocarpus microphyllus, Rícinus communis and Rosmarinus officinalis in the composition of natural tonics for hair growth. To this end, a qualitative bibliographic review was carried out in which criteria were adopted that include documents of a scientific nature that were related to the applicability of vegetable oils in cosmetics for hair growth, especially tonic lotions. In this context, vegetable oils stand out as an important constituent that add value to the product which is incorporated, promoting less abrasive therapeutic actions to users, sustainability and economic potential generated by family farming. Vegetable oils from Pilocarpus microphyllus, Ricino communis and Rosmarinus officinalis L. showed common characteristics for the antimicrobial, vasodilator and unblocking treatment of hair follicles, and can be used for incorporation in tonics for hair growth. It is suggested further research of experimental nature in vitro and in vivo about the incorporation of vegetable oils in formulations for hair growth.